Demand uncertainty, inventory and business cycles - Tamegawa, Kenichi (Journal of Business Economics and Management, 2014)
This paper introduces demand uncertainty and inventory into a dynamic stochastic general equilibrium model. We assume that firms must predict demand before production. The purpose of this study is to investigate the effects of several exogenous shocks on the model economy in our settings. A numerical simulation using our model shows the following results. When shocks that raise expected demand are given, inventory stocks increase because output exceeds demand. In the next period, firms release the inventory stock, reducing excess stock and decreasing output. Thus, inventory adjustment causes recession. This result implies that cyclical movement (economic boom and bust) continues until variables return to the steady state. Furthermore, we confirm that our model can reproduce stylized facts for inventory movements and enhance empirical fit relative to the model without inventory.